﻿ Solve 2x^3-3x^2-3x+2=0 | Uniteasy.com

Solve the cubic equation:

$$2x^3-3x^2-3x+2=0$$

Since the discriminant $$\Delta <0$$, the cubic equation has three distinct real roots.

$$\Delta=-0.421875$$

$$\begin{cases} x_1=\dfrac{1}{2} \\ x_2=\dfrac{1}{2}+\dfrac{3}{2} \\ x_3=\dfrac{1}{2}-\dfrac{3}{2} \end{cases}$$

In decimals,

$$\begin{cases} x_1=0.5 \\ x_2=2 \\ x_3=-1 \end{cases}$$

Detailed Steps on Solution

If a cubic equation has a rational root, the root could be a fracion number with a factor of constant term as the numerator and a factor of the coefficient of leading term as the denumerator.

1. Factorization Method

Find all possible factors for constant $$2$$, which are,

$$1, 2$$

$$-1, -2$$

and all possible factors of the coefficient of the leading term $$2$$,

$$1, 2$$

$$-1, -2$$

Dividing factors of constant term by those of the cubic term one by one gives the following fractions.

$$1, -1, 2, -2, \dfrac{1}{2}, -\dfrac{1}{2},$$

Substitute the fractions to the function $$f(x) = 2x³ - 3x² - 3x + 2$$ one by one to find out the one that makes $$f(x) = 0$$.

According to the factor theorem, $$f(n) = 0$$, if and only if the polynomial $$2x³ - 3x² - 3x + 2$$ has a factor $$x-n$$, that is, $$x=n$$ is the root of the equation.

Fortunetely, one of the numbers is found to make the equation equal.

$$f(-1) = 2(-1)³ - 3(-1)² - 3(-1) + 2 = 0$$

then, $$x = -1$$ is one of roots of the cubic equaiton $$2x³ - 3x² - 3x + 2 = 0$$. And, the equation can be factored as

$$(x +1)(ax^2+bx+c) = 0$$

Next we can use either long division or synthetic division to determine the expression of trinomial

Long division

Divide the polynomial $$2x³ - 3x² - 3x + 2$$ by $$x + 1$$

 2x² -5x 2 x + 1 2x³ -3x² -3x 2 2x³ +2x² -5x² -3x -5x² -5x 2x 2 2x 2 0

Now we get another factor of the cubic equation $$2x² - 5x + 2$$

Solve the quadratic equation: $$2x² - 5x + 2 = 0$$

Find factors of trinomial

Create a table of all factors for constant of $$2$$

$$\begin{array}{|c|} \hline1\times2\\ \hline(-1)\times (-2)\\ \hline\end{array}$$

Create another table of all factors for coeffcient of quadratic term $$2$$

$$\begin{array}{|c|} \hline1\times2\\ \hline(-1)\times (-2)\\ \hline\end{array}$$

Determine the roots by factorizing

Cross multiply the pairs from constant and leading term to find pairs of which the sum of products is equal to the coefficient of linear term 2

$$\begin{array}{|c|} \hline1\times1 + 2\times2 = 5\\ \hline1\times2 + 2\times1 = 4\\ \hline1\times(-1) + 2\times(-2) = -5\\ \hline\end{array}$$

The pair $$1\times(-1) + 2\times(-2) = -5$$ is found to satisfy the rule.

Then, the quadratic equaiton is factored as

$$(x - 2)(2x - 1) = 0$$

which results in another two roots

$$x_2 = 2$$

$$x_3 = \dfrac{1}{2}$$

That is,

$$\begin{cases} t_2 =2 \\ t_3=\dfrac{1}{2} \end{cases}$$

Another method to find the roots of a general cubic equation is simplifing it to a depressed form. This method is applicable to all cases, especially to those difficult to find factors.

2. Convert to depressed cubic equation

The idea is to convert general form of cubic equation

$$ax^3+bx^2+cx+d = 0$$

to the form without quadratic term.

$$t^3+pt+q = 0$$

By substituting $$x$$ with $$t - \dfrac{b}{3a}$$, the general cubic equation could be transformed to

$$t^3+\dfrac{3ac-b^2}{3a^2}t+\dfrac{2b^3-9abc+27a^2d}{27a^3} = 0$$

Compare with the depressed cubic equation. Then,

$$p = \dfrac{3ac-b^2}{3a^2}$$

$$q = \dfrac{2b^3-9abc+27a^2d}{27a^3}$$

Substitute the values of coefficients, $$p, q$$ is obtained as

$$p = \dfrac{3\cdot 2\cdot (-3)-(-3)^2}{3\cdot 2^2}=-\dfrac{9}{4}$$

$$q = \dfrac{2\cdot (-3)^3-9\cdot2\cdot (-3)\cdot (-3)+27\cdot 2^2\cdot2}{27\cdot 2^3}=0$$

Use the substitution to transform

Let $$p$$ and $$q$$ being the coefficient of the linean and constant terms, the depressed cubic equation is expressed as.

$$t^3 +pt+q=0$$

Let $$x=t+\dfrac{1}{2}$$

The cubic equation $$2x³ - 3x² - 3x + 2=0$$ is transformed to

$$t^3 -\dfrac{9}{4}t=0$$

For this equation, we have $$p=-\dfrac{9}{4}$$ and $$q = 0$$

Factor out common factor

Since each term contains a common factor, we can factor out the common factor $$x$$ out of each term.

$$(4t² - 9)t = 0$$

In order for the equation to hold true, either of the factors is equal to 0. Then, we get the first root,

$$t_1 = 0$$

$$4t² - 9 = 0$$

And then, the problem turns to solving a quadratic equation.

Solve the quadratic equation: $$4x² - 9 = 0$$

$$4t^2 = 9$$

Solving for $$t$$.

Then,

\begin{aligned} \\ t&=\pm \sqrt{\dfrac{9}{4}}\\ &=\pm \sqrt{\dfrac{3^2}{2^2}}\\ &=\pm \dfrac{3}{2}\\ \end{aligned}

That is,

$$\begin{cases} t_2 =\dfrac{3}{2} \\ t_3=-\dfrac{3}{2} \end{cases}$$

Since $$x = t - \dfrac{b}{3a}$$, substituting the values of $$t$$, $$a$$ and $$b$$ gives

$$x_1 = t_1+\dfrac{1}{2}=\dfrac{1}{2}$$

$$x_2 = t_2+\dfrac{1}{2}=\dfrac{1}{2}+\dfrac{3}{2}$$

$$x_3 = t_3+\dfrac{1}{2}=\dfrac{1}{2}-\dfrac{3}{2}$$

3. Summary

In summary, we have tried the method of factorization, cubic root formula to explore the solutions of the equation. The cubic equation $$2x³ - 3x² - 3x + 2=0$$ is found to have three real roots . Exact values and approximations are given below.

$$\begin{cases} x_1=\dfrac{1}{2} \\ x_2=\dfrac{1}{2}+\dfrac{3}{2} \\ x_3=\dfrac{1}{2}-\dfrac{3}{2} \end{cases}$$

Convert to decimals,

$$\begin{cases} x_1=0.5 \\ x_2=2 \\ x_3=-1 \end{cases}$$

Using the method of factorization, the roots are derived to the following forms

$$\begin{cases} x_1=-1 \\ x_2=\dfrac{1}{2} \\ x_3=2 \end{cases}$$

4. Graph for the function $$f(x) = 2x³ - 3x² - 3x + 2$$

Since the discriminat is less than zero, the curve of the cubic function $$f(x) = 2x³ - 3x² - 3x + 2$$ has 3 intersection points with horizontal axis.

Scroll to Top